Numerical study of cold-formed steel channel sections under combined web crippling and bending action - Janarthanan, B.; Mahendran, M. (ELSEVIER, 2020)
Cold-formed steel sections used in floor systems are vulnerable to web crippling, and with increasing span lengths, they are likely to fail under combined web crippling and bending action. A numerical study was therefore undertaken to investigate the combined web crippling-bending interaction behaviour of unlipped channel sections used as bearers in floor systems with fastened supports. Web crippling finite element models developed and validated by the authors in a recent study were extended to investigate the behaviour of unlipped channels under combined action of web crippling and bending while new finite element models were developed for bending and validated using available experimental results. All three types of finite element models were used in a detailed parametric study to obtain the capacities of 12 unlipped channel sections made of G250 and G450 steels under pure and combined web crippling and bending actions. Comparison of the combined web crippling and bending capacities obtained from finite element analyses with the interaction equations in three cold-formed steel design standards, AISI S100, AS/NZS 4600 and Eurocode 3 Part 1.3, showed that the current design equations are accurate for 50 mm bearing length. However, they can also be used to predict the combined web crippling-bending capacities conservatively for bearing lengths of 100 and 150 mm. A new design equation with a suitable capacity reduction factor was then proposed to improve the accuracy of predicting the mid-span load capacity of channel sections subject to combined web crippling and bending actions.
Keywords: Cold-formed steel beams; Web crippling failure; Combined web crippling and bending; Finite element analysis; Design equations